Development of the ClinESSDAI: a clinical score without biological domain. A tool for biological studies. Issue 11 (25th January 2016) - Seror, Raphaèle; Meiners, Petra; Baron, Gabriel; Bootsma, Hendrika; Bowman, Simon J; Vitali, Claudio; Gottenberg, Jacques-Eric; Theander, Elke; Tzioufas, Athanasios; De Vita, Salvatore; Ramos-Casals, Manel; Dörner, Thomas; et al.
Abstract : Objective: To develop and validate ClinESSDAI (Clinical European League Against Rheumatism Sjögren's Syndrome Disease Activity Index), ie, ESSDAI without the biological domain. Patients and methods: The 702 fictive vignettes derived from 96 real cases of primary Sjögren's syndrome of the ESSDAI development study were used. As for ESSDAI development, the physician assessment of disease activity (0–10 scale) was used as the 'gold standard' in a multivariate model for weighting domains, after removing the biological domain. The reliability, assessed by intraclass correlation coefficient (ICC) between ClinESSDAI and ESSDAI, explored if ClinESSDAI was equivalent to ESSDAI. Its psychometric (ie, measurement) properties were compared with that of ESSDAI in an independent cohort. Also, its use was evaluated on data of two clinical trials. Results: In multivariate modelling, all 11 domains remained significantly associated with disease activity, with slight modifications of some domain weights. Reliability between clinESSDAI and ESSDAI was excellent (ICC=0.98 and 0.99). Psychometric properties of clinESSDAI, disease activity levels and minimal clinically important improvement thresholds and its ability to detect change over time in clinical trials were very close to that of ESSDAI. Conclusions: ClinESSDAI appears valid and very close to the original ESSDAI. This score provides an accurate evaluation of disease activity independent of B-cell biomarkers. It could be used in various circumstances: (i) in biological/clinical studies to avoid data collinearity, (ii) in clinical trials, as secondary endpoint, to detect change independent of biological effect of the drug, (iii) in clinical practice to assess disease activity for visits where immunological tests have not been done.